Advances in 3D Bioprinting for Cancer Biology and Precision Medicine: From Matrix Design to Application. Issue 24 (15th August 2022) - Jung, MoonSun; Ghamrawi, Sarah; Du, Eric Y.; Gooding, J. Justin; Kavallaris, Maria
Abstract: The tumor microenvironment is highly complex owing to its heterogeneous composition and dynamic nature. This makes tumors difficult to replicate using traditional 2D cell culture models that are frequently used for studying tumor biology and drug screening. This often leads to poor translation of results between in vitro and in vivo and is reflected in the extremely low success rates of new candidate drugs delivered to the clinic. Therefore, there has been intense interest in developing 3D tumor models in the laboratory that are representative of the in vivo tumor microenvironment and patient samples. 3D bioprinting is an emerging technology that enables the biofabrication of structures with the virtue of providing accurate control over distribution of cells, biological molecules, and matrix scaffolding. This technology has the potential to bridge the gap between in vitro and in vivo by closely recapitulating the tumor microenvironment. Here, a brief overview of the tumor microenvironment is provided and key considerations in biofabrication of tumor models are discussed. Bioprinting techniques and choice of bioinks for both natural and synthetic polymers are also outlined. Lastly, current bioprinted tumor models are reviewed and the perspectives of how clinical applications can greatly benefit from 3D bioprinting technologies are offered. Abstract : 3D bioprinting enables the creation of 3D tumor‐like constructs in the laboratory by loading a mixture of cells and biomaterials. This review provides an overview of key considerations of the complex tumor microenvironment and matrix design when developing 3D tumor models. In this review, 3D bioprinted tumor models that are developed are highlighted and the main challenges for their clinical application discussed.